Fluorine-18 labelled building blocks for PET tracer synthesis. (13th June 2017) - van der Born, Dion; Pees, Anna; Poot, Alex J.; Orru, Romano V. A.; Windhorst, Albert D.; Vugts, Danielle J.
Abstract : This review presents a comprehensive overview of the synthesis and application of fluorine-18 labelled building blocks since 2010. Abstract : Positron emission tomography (PET) is an important driver for present day healthcare. Fluorine-18 is the most widely used radioisotope for PET imaging and a thorough overview of the available radiochemistry methodology is a prerequisite for selection of a synthetic approach for new fluorine-18 labelled PET tracers. These PET tracers can be synthesised either by late-stage radiofluorination, introducing fluorine-18 in the last step of the synthesis, or by a building block approach (also called modular build-up approach), introducing fluorine-18 in a fast and efficient manner in a building block, which is reacted further in one or multiple reaction steps to form the PET tracer. This review presents a comprehensive overview of the synthesis and application of fluorine-18 labelled building blocks since 2010.